Preliminary study on detection of Basal Stem Rot disease at oil palm trunk using electrical resistance - Esa, Nurnadiah (2016)
Basal Stem Rot (BSR) disease is one of the most crucial diseases that attacks oil palm tree in Malaysia. It is caused by the wood-rotting fungus known as Ganoderma boninense. Early detection is important in managing BSR disease spreads as this disease wills ultimately results with the destruction of the basal tissues of the plant where it can lead to the decrease in the production of Fresh Fruit Bunch (FFB) yield. This study was conducted to detect BSR disease at oil palm tree by using electrical resistance (ER). Ten samples of trees at the age of 25 years were investigated. LandMapper ERM-2 was used in detecting the disease by collecting ER values at eight positions surrounding the trunk at three different heights (0 cm, 60 cm and 120 cm) based on Wenner array principle. Kriging was conducted to interpolate the ER values inside the trunk as well as to classify the level of severity, which were identified as T1 (non-infected), T2 (mild level) and T3 (moderate level). Classification technique of geometrical interval with 2 classes was used to differentiate between the decay and non-decay area .Spatial analysis was then performed to calculate and compared between two areas. Healthy positions give higher ER values of more than 30Ω while the infected positions give less than 30Ω. Moreover, healthy tree had a higher mean values than the infected tree. Destruction of the basal tissues and presence of fruiting bodies were only seen at the height of 0 cm in severity level T2 and T3. By using Kriging, interpolation of decayed area was approximately having the same position with the origin of the decay area captured by DSLR camera. Descriptive statistics for the infected tree at 0 cm showed that the highest mean was 50.54Ω which was at level T1 while levels T2 and T3 had mean of 30.80Ω and 29.25Ω respectively. For Duncan test, it only differentiates between healthy tree and infected tree due to small differences between levels T2 and T3. Therefore, this approach sounds to be feasible in detecting BSR disease to prevent the loss of the oil palm tree stands.